Asr1 mediates glucose-hormone crosstalk by affecting sugar trafficking in tobacco plants - Dominguez, Pia Guadalupe (2013)
Asr (for ABA, stress, ripening) genes are exclusively found in the genomes of higher plants and the encoded proteins have been found localized both to the nucleus and cytoplasm. However, before the mechanisms underlying the activity of ASR proteins can be determined, the role of these proteins in planta should be deciphered. Results from the present study suggest that ASR is positioned within the signaling cascade of interactions among glucose, abscisic acid and gibberellins. Nicotiana tabacum transgenic lines with reduced levels of ASR protein showed impaired glucose metabolism and altered abscisic acid and gibberellin levels. These changes were associated with dwarfism, reduced CO2 assimilation and accelerated leaf senescence as a consequence of a fine regulation exerted by ASR to the glucose metabolism. This regulation resulted in an impact on glucose signaling mediated by hexokinase1 and SnRk1 (for Snf1-related kinase) which would subsequently have been responsible for photosynthesis, leaf senescence and hormone level alterations. It thus can be postulated that ASR is not only involved in the control of hexose uptake in heterotrophic organs, as we have previously reported, but also in the control of carbon fixation by the leaves mediated by a similar mechanism.